Formulation and Anti-Aging Activity of Collagen Extract from Yellowfin Tuna (Thunnus albacares) Skin Cream in UV-B Induced Wistar Rats - Jangga Jangga; Besse Yuliana; Abdul Wahid Suleman; Silvi Alfitri; Sulaiman Sulaiman (Direktorat Politeknik Kesehatan Makassar, 2026)
Skin aging is a progressive biological process that can be accelerated by excessive ultraviolet (UV) exposure, leading to structural damage characterized by wrinkle formation, loss of elasticity, and rough skin texture. This study aimed to formulate an anti-aging cream containing collagen-rich skin extract of yellowfin tuna (Thunnus albacares) and to evaluate its anti-aging efficacy in a UV-B–induced skin aging model using Wistar rats (Rattus norvegicus). A laboratory experimental design was employed using 15 male rats divided into five groups: negative control (cream base), positive control (commercial anti-aging cream), and treatment groups containing 1%, 3%, and 5% yellowfin tuna skin extract. The dorsal skin was exposed to UV-B radiation for 17 minutes daily for 10 consecutive days, followed by topical application of the respective formulations. Wrinkle severity was assessed macroscopically using a visual scoring system (0 = normal texture; 1 = shallow wrinkles; 2 = deep wrinkles with laxity). All formulations demonstrated acceptable physical stability, with pH values ranging from 4.98 to 5.48 and viscosity remaining within the acceptable range after cycling tests. Anti-aging evaluation revealed a dose-dependent improvement in wrinkle scores. The 5% formulation showed the most pronounced effect, with the median wrinkle score decreasing from 2 on day 1 to 0 on day 10, whereas the negative control group showed only a slight reduction from 2 to 1 during the same period. The 3% formulation demonstrated moderate improvement, while the 1% formulation exhibited fluctuating results. In conclusion, yellowfin tuna skin extract can be successfully formulated into a stable oil-in-water cream, and the 5% concentration exhibited the highest anti-aging activity in UV-B–exposed rats, supporting its potential as a marine-derived natural ingredient for topical anti-aging applications.